Large Normal and Intermediate Alleles in the Context of SCA2 Prenatal Diagnosis. Issue 1 (28th June 2013) - Cruz‐Mariño, Tania; Laffita‐Mesa, Jose Miguel; Gonzalez‐Zaldivar, Yanetza; Velazquez‐Santos, Miguel; Aguilera‐Rodriguez, Raul; Estupinan‐Rodriguez, Annelie; Vazquez‐Mojena, Yaime; Macleod, Patrick; Paneque, Milena; Velazquez‐Perez, Luis
Abstract: In 2001 a program for predictive testing of Spinocerebellar Ataxia type 2 was developed in Cuba, based on the detection of an abnormal CAG trinucleotide repeat expansion in the ATXN2 gene. A descriptive study was designed to assess the implications of ATXN2 large normal and intermediate alleles in the context of the SCA2 Prenatal Diagnosis Program. Four clinical scenarios were selected based upon the behaviour of large normal and intermediate alleles when passing from one generation to the next, showing expansions, contractions, or stability in the CAG repeat size. In some populations, traditional Mendelian risk figures of 0 % or 50 % may not be applicable due to the high frequency of unstable large normal alleles. Couples with no family history of SCA2 may have a >0 % risk of having an affected offspring. Similarly, couples in which there is both an expanded and a large normal allele may have a recurrence risk >50 %. It is imperative that these issues be addressed with these couples during genetic counseling. These recurrence risks have to be carefully estimated in the presence of such alleles (particularly alleles ≥27 CAG repeats), carriers need to be aware of the potential risk for their descendants, and programs for prenatal diagnosis must be available for them.